Social assistance and informal social networks and the resilience of the population in Ukraine - Kupenko, Olena; Ivanova, Tetyana; Kostenko, Andriana; Opanasiuk, Valentyna (International social security review (English edition), 2025)
Resilience is conceptualized as a property of subjects (individuals, families, households, communities, or nations) and is intrinsically linked to coping with and overcoming vulnerability, indicating that subjects may require external assistance during crises. Ukraine's social protection system during the Russian‐Ukrainian war has demonstrated sufficient resilience in protecting against life‐cycle risks. The State has also responded rapidly to the emergency crisis of war. International humanitarian organizations likewise have responded rapidly with numerous humanitarian aid programmes. However, funding opportunities are diminishing. This requires the most efficient use of limited resources. This study implements a community‐oriented approach, with a focus on localization in risk distribution through an analysis of monitoring data produced by international organizations and local research in Ukrainian communities. Key findings include overestimated expectations of family and friend support coupled with underestimated self‐reliance (approximately 20 per cent) during 2022–2024. Institutional support (volunteer, public, and international organizations) showed increased significance, while overall self‐reliance decreased in favour of external support sources. Future research directions include analysing expected‐versus‐actual assistance dynamics, investigating social support structure change factors, examining social trust transformation across institutions, and developing optimized support resource distribution programmes. La résilience est conceptualisée comme une propriété de sujets (individus, familles, ménages, communautés ou nations) et est étroitement liée à la capacité à faire face aux vulnérabilités et à les combattre. Ainsi, les sujets peuvent avoir besoin d’une aide extérieure en cas de crise. Durant la guerre opposant la Russie à l’Ukraine, le système de protection sociale ukrainien a fait montre de suffisamment de résilience pour protéger les populations contre les risques de l’existence. L’État a lui aussi rapidement pris des mesures d’urgence face à la guerre, à l’instar des organisations humanitaires internationales, qui ont déployé de nombreux programmes d’aide humanitaire. Toutefois, les possibilités de financement se réduisent comme peau de chagrin, ce qui implique une utilisation la plus efficiente possible de ressources limitées. Cette étude adopte une approche communautaire et met l’accent sur la localisation de la répartition des risques, en analysant les données de suivi d’organisations internationales et de recherches locales menées au sein des communautés ukrainiennes. Une surestimation des attentes en matière de soutien familial et amical ainsi qu’une sous‐estimation de l’autonomie (environ 20 pour cent) figurent parmi les principales conclusions pour la période 2022‐2024. Le soutien institutionnel (organisations bénévoles, publiques et internationales) a gagné en importance, tandis que l’autonomie a, dans l’ensemble, diminué au profit de sources d’aide externes. Les recherches futures devront comparer les dynamiques d’aide escomptées par rapport à celles mises en place, examiner les facteurs de changement touchant la structure de l’aide sociale, étudier la transformation de la confiance sociale entre les institutions et élaborer des programmes optimisés de répartition des ressources d’aide, entre autres. La resiliencia se conceptualiza como una propiedad que tienen distintos sujetos (personas, familias, hogares, comunidades o países) y que tiene que ver intrínsecamente con el hecho de hacer frente a la vulnerabilidad y superarla, lo cual indica que es posible que los sujetos requieran de ayuda externa durante las crisis. El sistema de protección social de Ucrania durante la guerra entre Rusia y Ucrania ha demostrado la resiliencia suficiente en la protección frente a los riesgos del ciclo de vida. El Estado también ha respondido con rapidez a la situación de emergencia derivada de la guerra. De forma similar, las organizaciones humanitarias internacionales han reaccionado rápidamente con numerosos programas de ayuda humanitaria. Sin embargo, las oportunidades de financiación están disminuyendo, lo que requiere hacer un uso lo más eficiente posible de los recursos limitados. En el presente estudio se aplica un enfoque orientado a la comunidad, con especial atención a la localización en la distribución de los riesgos, mediante un análisis de los datos de seguimiento generados por organizaciones internacionales e investigaciones locales en comunidades ucranianas. Una de las principales conclusiones es que, en el periodo 2022‐2024, se sobreestimó el apoyo de familiares y amigos, pero se subestimó la capacidad de las personas para ayudarse a sí mismas (aproximadamente el 20 por ciento). El apoyo institucional (organizaciones internacionales, públicas y de voluntariado) ha tenido cada vez más relevancia, mientras que la autosuficiencia ha ido disminuyendo en beneficio de las fuentes de apoyo externo. Futuras líneas de investigación pueden ser el análisis de las dinámicas asistenciales actuales en comparación con las esperadas, la investigación de factores de cambio de las estructuras de apoyo social, el estudio de la transformación de la confianza social en las instituciones, y el desarrollo de programas optimizados de distribución de recursos de apoyo. Widerstandsfähigkeit wird hier als Eigenschaft von Subjekten – also Individuen, Familien, Haushalten, Gemeinschaften oder Nationen – verstanden und ist untrennbar mit der Bewältigung und Überwindung von Gefährdungen verbunden. Dies impliziert, dass Subjekte in Krisenzeiten auf externe Unterstützung angewiesen sein können. Das ukrainische Sozialschutzsystem hat sich im Verlauf des russisch‐ukrainischen Krieges als weitgehend widerstandsfähig im Schutz vor lebenszyklusbedingten Risiken erwiesen. Der Staat reagierte zudem zügig auf die kriegsbedingte Notlage. Auch internationale humanitäre Organisationen setzten rasch zahlreiche Hilfsprogramme um. Allerdings nehmen die verfügbaren Finanzmittel ab, was eine möglichst effiziente Nutzung der begrenzten Ressourcen erforderlich macht. In dieser Studie wird ein gemeindeorientierter Ansatz verfolgt, der den Fokus auf die Lokalisierung der Risikoverteilung legt. Grundlage dafür ist die Analyse von Überwachungsdaten internationaler Organisationen sowie lokaler Erhebungen in ukrainischen Gemeinden. Zu den wichtigsten Erkenntnissen gehört, dass im Zeitraum 2022–2024 die Unterstützung durch Familie und Freunde überschätzt, die eigene Fähigkeit zur Selbsthilfe jedoch unterschätzt wurde (etwa 20 Prozent). Die Bedeutung institutioneller Unterstützung – etwa durch Freiwillige, öffentliche Stellen und internationale Organisationen – hat zugenommen, während die Fähigkeit zur Selbsthilfe der Menschen insgesamt zugunsten externer Unterstützungsquellen abnahm. Künftige Forschungsvorhaben sollten die Dynamik zwischen erwarteter und tatsächlicher Unterstützung analysieren, Faktoren des Wandels in sozialen Unterstützungsstrukturen untersuchen, den Wandel des sozialen Vertrauens gegenüber verschiedenen Institutionen betrachten und Programme zur optimierten Verteilung von Unterstützungsressourcen entwickeln. Устойчивость концептуально определяется как свойство субъектов (отдельных лиц, семей, домохозяйств, сообществ или наций) и неразрывно связана с преодолением уязвимости, что указывает на то, что субъектам может потребоваться внешняя помощь во время кризисов. Система социальной защиты Украины во время российско‐украинской войны продемонстрировала достаточную устойчивость в защите от рисков жизненного цикла. Государство также быстро отреагировало на чрезвычайный кризис войны. Международные гуманитарные организации также оперативно отреагировали многочисленными программами гуманитарной помощи. Однако возможности финансирования сокращаются. Это требует максимально эффективного использования ограниченных ресурсов. В этом исследовании реализован подход, ориентированный на сообщество, с упором на локализацию распределения риска посредством анализа данных мониторинга, предоставляемых международными организациями, и локальных исследований в украинских сообществах. Основные выводы включают завышенные ожидания поддержки со стороны семьи и друзей в сочетании с заниженным уровнем самообеспечения (примерно на 20 процентов) в течение 2022–2024 годов. Организационная поддержка (волонтерские, общественные и международные организации) продемонстрировала возросшую значимость, в то время как общий уровень самообеспечения снизился в пользу внешних источников поддержки. Будущие направления исследований включают анализ ожидаемой и фактической динамики помощи, изучение факторов изменения структуры социальной поддержки, изучение трансформации социального доверия в различных организациях и разработку оптимизированных программ распределения ресурсов поддержки. 韧性被概念化为主体(个人、家庭、户、社区或国家)的属性, 与应对和克服脆弱性密切相关, 表明主体在危机时期可能需要外部援助。俄乌战争期间, 乌克兰社会保护体系展现出足够的韧性来抵御生命周期风险。国家对战争紧急危机迅速作出响应。国际人道主义组织同样响应迅速, 实施多项人道主义援助计划。然而, 资金机会正在减少, 这要求最有效地利用有限的资源。本研究采用社区导向方法, 通过分析国际组织监测数据及乌克兰本土社区研究, 重点关注风险分布的本地化特征。关键发现包括:2022‐2024年间对亲友支持的预期被高估, 而对自力更生的预期被低估(约20%)。制度性支持(志愿者、公共机构和国际组织)的重要性上升, 而整体自力更生程度下降, 转而依赖外部支持来源。未来研究方向包括分析预期援助与实际获助的动态差异、探究社会支持结构变迁因素、研究跨机构社会信任转型, 以及制定优化支持资源分配方案。 ُنظر إلى القدرة على الصمود على أنها سمة من سمات الكيانات (الأفراد أو العائلات أو الأسر المعيشية أو المجتمعات المحلية أو الأمم)، وترتبط ارتباطًا جوهريًا بالتعامل مع الضعف والتغلب عليه، مما يشير إلى أن الأفراد قد يحتاجون إلى مساعدة خارجية أثناء الأزمات. وقد أظهر نظام الحماية الاجتماعية في أوكرانيا خلال الحرب الروسية الأوكرانية قدرة صمود كافية فيما يتعلق بالحماية من مخاطر دورة الحياة. كما استجابت الدولة بسرعة لأزمة الطوارئ الناجمة عن الحرب. وبالمثل، استجابت المنظمات الإنسانية الدولية بسرعة من خلال العديد من برامج المساعدة الإنسانية. ومع ذلك، فإن فرص التمويل آخذة في التضاؤل، مما يتطلب الاستخدام الأمثل للموارد المحدودة. وتطبق هذه الدراسة نهجًا مجتمعيًا، مع التركيز على التوزيع المحلي للمخاطر من خلال تحليل بيانا